Ethics and religion as drivers of brand identity involvement: Evidence from Sharia insurance in Indonesia and Malaysia - Dina Lusianti; Ken Sudarti; Agung Prihandono (Jurnal Manajemen dan Pemasaran Jasa, 2025)
Brand marketing strategies grounded in ethics and religious values are an interesting topic to explore. Consumers tend to view the presence of a brand as personal, creating value through co-creation. Although not always, religion can play an important role in shaping brand loyalty. This study aims to analyze the effect of religious brand resonance on brand loyalty, with brand purity and brand love as mediating dimensions of brand identity. This study has a crucial point, considering the right marketing strategy policy for the target consumer market that is sensitive to personal preferences. This latest study integrates identity theory in religious brand resonance by exploring the construction of brand identity involvement. The survey method was used, with questionnaires distributed to 428 respondents in Indonesia and Malaysia. With the snowball sampling technique, data on the responses of Sharia Insurance Policyholders have been obtained. The results of the study indicate that religious brand resonance has a positive and significant effect on brand loyalty. Brand purity and brand love appear as mediating variables between religious brand resonance and brand loyalty. The findings of this study imply the need for a brand marketing strategy by building a brand that is relevant to the identity of the religious brand, and maintaining quality consistently to maintain brand loyalty.